Reliability of biometric devices for measuring hand grip and finger pinch strength in stroke patients over 50: a prospective observational study - Justyna Leszczak; Bogumiła Pniak; Joanna Baran; Agnieszka Guzik (Scientific Reports)
Abstract The aim of the study was to assess the test–retest reliability, inter-rater reliability of the Biometrics device with regard to hand grip and finger pinch strength in people in the late period after stroke aged over 50 years. A total of 100 individuals in the late period after stroke participated in the study. Two investigators performed hand grip and pinch strength measurements using the Biometrics E-link assessment system. The subjects were examined twice within two weeks, under the same conditions. After conducting the examinations, high consistency of measurements was found both between the investigators and between the examinations using a hand grip dynamometer and a Pinchmeter. For all measurements, high values of Pearson correlation coefficient close to 1, interclass correlation coefficient (ICC) > 0.9 and Cronbach’s alpha index > 0.9 were shown. The width of the LoA interval in the pinchometer measurements (comparison of Study I vs. II for the same examiner) often oscillated around the value of 1.0 or less. In the dynamometer, the results showed repeatability for the right hand (for examiner I: LoA was 3.984; examiner II: LoA–3.470. The study showed that hand grip and pinch strength assessment performed using the Biometrics E-link assessment system show high test–retest reliability and inter-rater reliability. The Biometrics E-link can be recommended for daily clinical practice among people in the late period after stroke.